2022
DOI: 10.1108/f-01-2022-0006
|View full text |Cite
|
Sign up to set email alerts
|

Converting commercial and industrial property into rented residential accommodation: development of a decision support tool

Abstract: Purpose This study aims to develop a decision-making tool that assesses the economic feasibility of converting commercial and industrial buildings into rented residential accommodation. This tool also enables developers to provide high-quality rented residential accommodation that contribute to the gentrification of formerly industrialised inner city or developed areas. Design/methodology/approach The overarching epistemological approach adopted used inductive reasoning and a postpositivist philosophical des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…This paper's findings suggest the existence of multiple contractual amendments when procuring MMC projects. Results reflect the tendency of such amendments to focus on liquidated damages and retention amounts, both of which align with Taylor et al (2022) discussions in the UK context. Overall, despite the findings suggesting the popularity of the standard forms, amendments exist nevertheless, and the original clauses are modified to reflect changes (Noruwa et al, 2022).…”
Section: Regular Contractual Amendmentssupporting
confidence: 78%
“…This paper's findings suggest the existence of multiple contractual amendments when procuring MMC projects. Results reflect the tendency of such amendments to focus on liquidated damages and retention amounts, both of which align with Taylor et al (2022) discussions in the UK context. Overall, despite the findings suggesting the popularity of the standard forms, amendments exist nevertheless, and the original clauses are modified to reflect changes (Noruwa et al, 2022).…”
Section: Regular Contractual Amendmentssupporting
confidence: 78%
“…As an iterative waterfall process was adopted [33,34], this research first defines the research scope, then searches for pertinent studies prior to analysing the search outcomes and categorising the results based on a psychological climate model developed by Hall, Dollard and Coward [9] (cf. Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…: (1) identifying knowledge base elements of CMO (see Figure 1); (2) sampling and data collection; (3) data analysis (root causes analysis); (4) multiple triangulation-based validation. The research undertaken was governed by a strict ethical protocol guiding this work that included: anonymising all participants' demographic details; holding all information in a secure location and neither disseminating nor divulging to any third party without their express permission in writing; ensuring all participants could access results in aggregate form post research completion [85][86][87]. Thus, these four main steps of the methodology followed in this research are shown in Figure 2, and further details and clarifications are demonstrated in the following sub-sections.…”
Section: Methodsmentioning
confidence: 99%